Taurine potentiates artemisinin efficacy against malaria by modulating the immune response in Plasmodium berghei-infected mice - Xin Li; Ning Jiang; Qilong Li; Kexin Zheng; Yiwei Zhang; Xiaoyu Sang; Ying Feng; Ran Chen; Qijun Chen (Parasites & Vectors)
Abstract Background Artemisinin (ART) is a frontline drug for the treatment of malaria; however, the emergence of ART-resistant Plasmodium strains necessitates increasing ART sensitivity. Given that taurine (TAU) has been shown to have immunomodulatory activity, we investigated the effects of TAU as an adjunct therapy to ART in mice infected with Plasmodium berghei. Methods Mice infected with P. berghei ANKA strain (P. berghei ANKA) were treated with TAU alone, ART alone or a combination of TAU and ART (TAU + ART), and their survival time and parasitaemia were recorded. The cytotoxic effects of TAU and ART were subsequently assessed. The expression levels of inflammasome-related genes and inflammatory factors in mice infected with P. berghei ANKA were analysed in relation to those in mice treated with TAU alone, ART alone or the TAU + ART combination. The therapeutic effects were further evaluated by histological analysis and measurement of the spleen index. Results Compared with the control mice, P. berghei ANKA-infected mice treated with ART in combination with TAU presented significantly lower parasitaemia and prolonged survival. The combined treatment resulted in significant reductions in the expression levels of inflammasome-related genes in the spleen, including absent in melanoma 2 (AIM2), caspase-1, NOD-, LRR- and pyrin domain-containing protein 3 (Nlrp3), Nlrp1b, Nlrp1b, NLR family CARD domain containing 4 (Nlrc4), Nlrp6, nucleotide binding oligomerization domain containing 1 (NOD1) and NOD2, and decreases in the levels of inflammatory cytokines in the serum, including interleukin (IL)-12p70, tumour necrosis factor-alpha, monocyte chemoattractant protein-1, IL-10 and IL-6. Histopathological analysis confirmed that TAU + ART combination treatment reduced spleen pathology caused by P. berghei ANKA infection. Conclusions The findings indicate that TAU potentiates ART efficacy by modulating the immune response in P. berghei-infected mice. Graphical Abstract